Global Emissions: A New Contribution from the Shadow Economy - Canh, Nguyen Phuc; Thanh, Su Dinh; Schinckus, Christophe; Bensemann, Jo; Thanh, Lai Trung (International Journal of Energy Economics and Policy, 2019)
Based on the STIRPAT model and the EKC hypothesis, this study provides new evidences on the economic determinants of global emissions. The system-GMM estimations are used for the sample of 106 economies in the period of 1995-2012 to investigate the influences of income level, urbanization, industrialization, energy intensity, public expenditure, trade openness, FDI inflow, and especially shadow economy on total greenhouse emissions, CO2 emissions, CH4 emissions, and N2O emissions, respectively. This study contributes to the literature in three folds. First, the industrialization energy intensity are the main drivers for all emissions (excluding N2O). While, urbanization has positive effects on emissions excluding the case of CH4. Other drivers including public spending and economic integration (proxied by trade openness and FDI inflow) are also tested with interesting findings. Second, a higher level of shadow economy increases all emissions excluding CO2. Third, the determinants of emissions vary depending on the countries' income level. The study is supported by a battery of robustness checks and by various estimations in the short and long-run to identify the importance of emissions' drivers. Keywords: Emissions; CO2, CH4, N2O, Public expenditures, Economic integration, Shadow economy. JEL Classifications: F18, F64, O44, Q56, R11, O17 DOI: https://doi.org/10.32479/ijeep.7244